Hard cheese: upland pastoralism in the Italian Bronze and Iron Ages - Pearce, Mark (JR Collis Publications, 2016)
By moving livestock to summer farms, fodder at the home base is saved but the milk and other animal products produced during the animals’ absence are no longer immediately available to those left at the home base. In this paper I shall explore the economic implications of the use of summer farms, in particular the effect on carrying capacity, on the number of livestock which can be over-wintered, and on the use of the milk produced while the animals are at the summer grazing lands.